Children of the "Volk" : children's literature as an ideological tool in National Socialist Germany - Robertson, Stephanie 1988- (Kinder- und Jugendkultur, -literatur und -medien, 2018)
Inhaltsverzeichnis: Didacticism, ideology and defining children's literature -- Literary publication and discourse under National Socialism -- Mädchen- und Jungenbacher under National Socialism -- From doctors to butchers: anti-Semitic and racial representations -- Conclusion.